NEUROPROTECTIVE EFFECT OF RESVERATROL ON VALPROIC ACID INDUCED OXIDATIVE STRESS AUTISM IN SWISS ALBINO MICE (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The present research work is aimed to investigate the anti-oxidant/neuroprotective role of Resveratrol in reversing the valproic acid induced autism in postnatal swiss albino mice. Separate 13 day old/ Post natal day (PND) 13 swiss albino mice of either sex into 5 groups, each group consists of six mice of either sex, groups namely Group I - Control, Group II - Resveratrol, Group III - Negative control, Group IV & V - Resveratrol treatment groups. On PND 14 administer single dose of Valproic acid (VPA) or Sodium Valproate (400 mg/kg, subcutaneously) to III, IV & V groups to induce autism. Treatment is given in two doses 10 mg/kg, intraperitoneally (i.p) as Low dose and 40 mg/kg, i.p as High dose from the 13th day to the end of study. Assessment of autism is done by different behavioral screening methods during PND 14 to 40. Treatment with resveratrol significantly decline the autism symptoms compared with negative control. At the end of study on PND 41 all the animals were sacrificed to assess the biochemical estimations like Anticholinesterase enzyme, Total Protein, antioxidant enzyme (Catalase, Superoxide and Glutathione) activity and cerebellar histopathological examination. Treatment with Resveratrol has shown a significant beneficial difference on behavioral alterations, oxidative markers, neurotransmitters, and restoration of the altered purkinje cells of autism. This research work we conclude that resvertrol have a potent anti-oxidant, neuroprotective, anxiolytic, learning & memory enhancing agent against valproic acid induced autism.